2021
DOI: 10.2478/orga-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout and Counterproductive Work Behaviour of the Jordanian Bank Employees

Abstract: Background/Purpose: This study investigated the relationship between job burnout and counterproductive work behavior (CWB) among 307 employees drawn from various banks within Jordan. This study also examined the levels of job burnout and CWB with regard to gender, age, marital status, and education. Methodology: For data collection, the convenience sampling method is utilized to survey frontline bank employees. The Oldenburg Burnout Inventory scale, which assesses exhaustion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…As the psychological and personal strain that results in burnout increases, employees are more likely to exhibit CWB's (Azam et al, 2022). Lubbadeh (2021) came to similar conclusions in his study, finding that as individuals' burnout levels increase, CWB's also increase.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…As the psychological and personal strain that results in burnout increases, employees are more likely to exhibit CWB's (Azam et al, 2022). Lubbadeh (2021) came to similar conclusions in his study, finding that as individuals' burnout levels increase, CWB's also increase.…”
Section: Discussionmentioning
confidence: 56%
“…Previous research has demonstrated that burnout is significantly related to CWB's and can have a significant impact on their occurrence. For instance, Lubbadeh's (2021) study identified significant associations between burnout and CWB's, indicating that burnout has a considerable impact on the occurrence of such behaviors. Similarly, Azam et al (2022) observed that burnout was positively related to CWB's, suggesting that higher levels of burnout could lead to increased occurrences of such behaviors.…”
Section: H1: There Is a Relationship Between Personality And Counterp...mentioning
confidence: 98%
“…The Mann-Whitney U test did not indicate any statistically significant differences between married and single respondents on the scales Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment Assessment (PA) (Table 7). According to the findings of a study conducted among Jordanian bank employees, there were no statistically significant differences in job burnout scores between single and married employees (Lubbadeh, 2021). Other studies have also found that both single and married employees experience the same level of occupational burnout (Haque & Aslam, 2011).…”
Section: Source: the Authorsmentioning
confidence: 95%
“…One of the major issues confronting employees in the banking sector is occupational burnout (Khalid et al, 2020;Tafi et al, 2022;Tehrani et al, 2021). Numerous studies have shown that employees in the banking sector are constantly under pressure due to heavy workload, rapid and intense technological changes, fierce competition, and responsibility for high financial results (Al-Kahtani & Allam, 2013;Awwad et al, 2022;Hashemnia et al, 2014;Iakymenko et al, 2015;Khattak et al, 2011;Koyuncu et al, 2021;Lubbadeh, 2021). The International Labor Organization identified a number of concerns that workers in the banking sector must cope with, including increased deadline pressure, ergonomic issues, an increase in violence, challenging and demanding clients (Giga & Hoel, 2003).…”
Section: Occupational Burnout In Banking Sectormentioning
confidence: 99%
“…For this reason, management fashions, mostly produced with neological expressions and concepts that do not have a counterpart in nature, emerge as approaches that can be grounded and do not have concrete counterparts. Management fashion approaches that have no scientific and operational value, management fashions that only waste time and mental effort; Organizational Silence continues with trendy concepts such as organizational citizenship, Job Burnout, Anti-productive Work Behaviors, Psychological Contract, Organizational Commitment and Organizational Trust (Under & Gerede, 2021;Al-Madadha et al, 2021;Lubbadeh, 2021;Huy et al, 2020; http://organizacija.fov.uni-mb.si/index.php/organizacija/article/view/1388Akkaya, 2020).…”
Section: Matrix Managementmentioning
confidence: 99%